Історічні відомості розробки сталей для конструкцій будівлі палацу з’їздів співробітниками УКРНДІМЕТу - Журило, Дмитро Юрійович; Міщенко, Марина Миколаївна (ГО "Всеукраїнська асамблея докторів наук з державного управління", 2023)
Метою статті є необхідність висвітлити основні віхи розробки сталей та їх призначення в 30-40 х роках ХХ ст., узагальнити пріоритетні наукові здобутки при виплавці сталей типу ДС, МС та кортену для Палацу з’їздів. На початку 1930-х років було розроблено декілька проектів московського Палацу з’їздів і за результатами конкурсу було обрано переможця. Світова практика не знала аналогів подібним будівлям. Споруда, висотою понад 400 метрів, повинна була символізувати перемогу нового політичного ладу. Саме для можливості цієї будівлі наприкінці 1931 р. було знищено храм Христа Спасителя. Передбачувана площа московського Палацу з’їздів становила 11 гектарів з об'ємом будівлі понад 7,5 млн. кубічних метрів (за об’ємом – це більше, ніж три піраміди Хеопса). Вага конструкцій московського Палацу з’їздів перевищувала 1,5 млн тон. Кожна колона каркаса відомого ньюйоркського хмарочоса «Емпайер Стейт Білдінг» (висотою 383 метри, на той момент він був найвищою будівлею в світі) тиснула на землю з силою в 4700 тон, а кожна колона вежі Палацу з’їздів повинна була нести навантаження від 8000 до 14000 тон. Загальна вага лише сталевих конструкцій перевищувала 350000 тон. Серйозні навантаження на сталевий каркас будівлі вимагали високоякісного металу. В 1939 році на базі Харківського Українського науково-дослідного інституту металів (УкрНДІМет), який було засновано в 1928 р., було виконано серйозну дослідницьку роботу з розробки технології виплавки і прокатки корозійностійкої сталі для побудови будівлі Палацу Рад. Роботами керував професор Євген Григорович Шумовський. Завдяки науково-дослідним роботам українських металургів було обрано три групи сталей, які, на перший погляд, найбільш підходили для використання при будівництві багатоповерхових будівель. Це були сталі ДС, МС та кортен. Маркування «МС» – це абревіатура «мало старіюча сталь», а «ДС» – «Дворец Съездов». Властивості сталі МС найбільш активно досліджували співробітник УкрНДІМету Мусій Аронович Гершгорн та заступник начальника технічного відділу металургії заводу ім. Михайла Фрунзе Роман Кирилович Попов. Було доведено, що для сталей, які містять мідь, не потрібно використання особливих методів нагрівання, режиму обтискання, використання спеціальної калібровки. Це здешевлювало та значно спрощувало технологію отримання прокату з таких сталей. Згодом технологію виплавляння вказаних сталей було опановано на більшості крупних заводів країни. Вже в 1940 році було розпочато монтаж каркаса будівлі Палацу з’їздів. Але почалася Друга світова війна і будівництво було заморожено. З демонтованого каркасу виготовляли протитанкові їжаки та протипіхотні загородження. Виконані дослідження дали подальшій розвиток металургії сталей з спеціальними властивостями в Україні та в СРСР, та на довгі роки стало орієнтиром для досліджень та фундаментом для стандартів з механічних досліджень сталей та інших конструкційних матеріалів.

The purpose of the article is to highlight the main milestones in the development of steels and their purpose in the 30-40s of the twentieth century, to summarize priority scientific achievements in the smelting of DS, MS and Corten steels for the palace of congresses. In the early 1930s, several projects of the Moscow Palace of congresses were developed and the winner was chosen based on the results of the competition. World practice has never known any analogues of such buildings. The building, which is more than 400 meters high, was supposed to symbolize the victory of the new political system. It was for the construction of this building that the beautiful cathedral of Christ the saviour was destroyed at the end of 1931. The estimated area of the Moscow Palace of congresses was 11 hectares with a building volume of more than 7,5 million square meters. cubic meters (by volume – this is more than the three pyramids of Cheops). The weight of the structures of the Moscow Palace of congresses exceeded 1,5 million tons. Each column of the frame of the famous New York skyscraper "Empire State Building" (383 meters high, at that time it was the tallest building in the world) pressed down on the ground with a force of 4,700 tons, and each column of the tower of the palace of congresses had to carry a load of 8 000 to 14 000 tons. The total weight of steel structures alone exceeded 350 000 tons. It is clear that serious loads on the steel frame of the building required high-quality metal. In 1939, on the basis of the Kharkov Ukrainian Research Institute of metals (UkrNDIMet), which was founded in 1928, serious research work was carried out on the development of technology for smelting and rolling corrosion-resistant steel for the construction of the Palace of Soviets building. The work was supervised by professor Evgeny Grigoryevich Shumovsky. Thanks to the research work of ukrainian metallurgists, three groups of steels were selected, which, at first glance, were most suitable for use in the construction of multi-storey buildings. They were DC, MS, and Corten steel. Marking "MS" is an abbreviation for "little aging steel", and "DS" - "is Palace of congresses". The properties of MS steel were most actively studied by Musiy Aronovich Gershhorn, an employee of UkrNDIMet, and Roman Kirillovich Popov, deputy head of the Technical Department of metallurgy at the Mikhail Frunze plant. It has been proven that Steels containing copper do not require the use of special heating methods, crimping mode, or the use of special calibration. This reduced the cost and greatly simplified the technology of obtaining rolled products from such steels. Within a year, the technology of smelting these steels was mastered at most large factories in the country. Already in 1940, the installation of the frame of the Palace of congresses building was started. But the Second World War began and construction was frozen. Anti-tank hedgehogs and anti-personnel barriers were made from the dismantled frame. The conducted research led to further development of metallurgy of steels with special properties in Ukraine and in the USSR, and for many years became a reference point for research and the foundation for standards for mechanical research of steels and other structural materials.
Historical information on the development of steels for structures of the palace of congresses building by employees of UKRNIIMET
Keywords: металургія; сталь; кортен; інститут металів; Палац з'їздів; metallurgy; steel; сorten; Institute of metals; Palace of congresses